Predicting fetoplacental chromosomal mosaicism during non‐invasive prenatal testing. (19th February 2018) - Brison, Nathalie; Neofytou, Maria; Dehaspe, Luc; Bayindir, Baran; Van Den Bogaert, Kris; Dardour, Leila; Peeters, Hilde; Van Esch, Hilde; Van Buggenhout, Griet; Vogels, Annick; de Ravel, Thomy; Legius, Eric; et al.
Abstract: Objective: Non‐invasive prenatal detection of aneuploidies can be achieved with high accuracy through sequencing of cell‐free maternal plasma DNA in the maternal blood plasma. However, false positive and negative non‐invasive prenatal testing (NIPT) results remain. Fetoplacental mosaicism is the main cause for false positive and false negative NIPT. We set out to develop a method to detect placental chromosomal mosaicism via genome‐wide circulating cell‐free maternal plasma DNA screening. Method: Aneuploidy detection was combined with fetal fraction determination to enable the detection of placental mosaicism. This pipeline was applied to whole genome sequencing data derived from 19 735 plasma samples. Following an abnormal NIPT, test results were validated by conventional invasive prenatal or postnatal genetic testing. Results: Respectively 3.2% (5/154), 12.8% (5/39), and 13.3% (2/15) of trisomies 21, 18, and 13 were predicted and confirmed to be mosaic. The incidence of other, rare autosomal trisomies was 0.3% (58/19, 735), 45 of which were predicted to be mosaic. Twin pregnancies with discordant fetal genotypes were predicted and confirmed. Conclusion: This approach permits the non‐invasive detection of fetal autosomal aneuploidies and identifies pregnancies with a high risk of fetoplacental mosaicism. Knowledge about the presence of chromosomal mosaicism in the placenta influences risk estimation, genetic counseling, and improves prenatal management. Abstract : What's already known about this topic? Non‐invasive prenatal detection of fetal aneuploidies can be achieved with high accuracy through sequencing of circulating cell‐free DNA (cfDNA) in maternal plasma. Current sequencing‐based bioinformatics pipelines report common trisomies 1–3 ignoring the status of other autosomal chromosomes and do not predict the presence of mosaicism What does this study add? The presented aneuploidy detection pipeline, combined with fetal fraction determination, permits the non‐invasive detection of aneuploidies in all chromosomes and pinpoints cases at high risk for fetoplacental mosaicism. Reporting about the presence of mosaicism in the placenta can influence risk estimation of a possible miscarriage, aid in the prenatal management, and improve genetic counseling in future pregnancies.